Comparison of MMP1 Gene Expression and Collagen Percentage in Response to Polydioxanone, Poly-L-Lactic Acid and Polycaprolactone Thread Implantation in Ageing Rat Skin - Putri, Fanny Karuna; Wargasetia, Teresa Liliana; Ratnawati, Hana (Scripta Medica, 2025)
Background/Aim: Photoageing causes collagen degradation, leading to sagging skin, increased wrinkles and rough surfaces as signs of skin ageing. UV-B radiation increases reactive oxygen species (ROS) production, affecting the mitogen-activated protein kinase (MAPK) pathways, resulting in the expression of the MMP1 gene, which can induce collagen fibre degradation. This study aimed to compare the MMP1 gene expression and collagen percentage in response to polydioxanone (PDO), poly-L-lactic acid (PLLA) and polycaprolactone (PCL) thread implantation in ageing rat skin. Methods: The study involved female Wistar rats, divided into six groups: young rats without UV-B exposure, old rats without UV-B exposure, ageing model rats exposed to UV-B and ageing model rats implanted with PDO, PLLA and PCL threads. UV-B exposure was given 3 times per week for 4 weeks with a total dose of 840 mJ/cm2. Parameters assessed included MMP1 gene expression and skin collagen percentage. Results: Data analysis showed that the ageing model skin organ had higher MMP1 gene expression (p < 0.05) and lower collagen percentage (p < 0.05) compared to young rats without UV-B exposure. MMP1 gene expression in the three thread implantation groups was equivalent to other groups (p > 0.05). Collagen percentage was equivalent in the three thread treatment groups (p > 0.05), higher (p < 0.05) than an ageing model, but did not differ (p > 0.05) from young rats without UV-B exposure. Conclusions: The study concludes that the implantation of the three types of threads, PDO, PLLA and PCL, does not reduce MMP1 gene expression but has an equivalent ability to increase collagen percentage in ageing rat models.